2020
DOI: 10.1002/clc.23489
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of sleep‐disordered breathing with pacemakers: Indexes for risk stratification of atrial fibrillation and risk of stroke

Abstract: Background: Sleep apnea (SA) is a risk factor for atrial fibrillation (AF). Advanced pacemakers are now able to calculate indexes of SA severity. Hypothesis: We investigated the changes in pacemaker-measured indexes of SA, we assessed their predictive value for AF occurrence and the associated risk of stroke and death at long-term. Methods: We enrolled 439 recipients of a pacemaker endowed with an algorithm for the calculation of a Respiratory Disturbance Index (RDI). The RDI variability was measured over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“… 13 Our results extend previous findings by demonstrating that the continuously measured weekly RDI values allow dynamic stratification for AHRE risk during follow-up, unlike the maximum RDI value calculated during the entire follow-up period. In agreement with pervious results obtained in pacemaker patients, 14 we observed a considerable variability in ICD-detected SA. This suggests the superiority of the continuous monitoring vs. a single overnight sleep study that may result in the misclassification of severe SA and is also hypothesized by other authors.…”
Section: Discussionsupporting
confidence: 93%
“… 13 Our results extend previous findings by demonstrating that the continuously measured weekly RDI values allow dynamic stratification for AHRE risk during follow-up, unlike the maximum RDI value calculated during the entire follow-up period. In agreement with pervious results obtained in pacemaker patients, 14 we observed a considerable variability in ICD-detected SA. This suggests the superiority of the continuous monitoring vs. a single overnight sleep study that may result in the misclassification of severe SA and is also hypothesized by other authors.…”
Section: Discussionsupporting
confidence: 93%
“…34 According to the authors, their findings explain the poorer efficacy of rhythm control strategies among AF cohorts with increasingly severe SA 35 and highlight paroxysmal AF cohorts with severe SA as a group well poised to derive maximal antiarrhythmic benefit from obstructive SA treatment, in agreement with previous evidence. 36 The availability of a reliable tool which allows automated detection of advanced SA together with continuous monitoring of the burden of AF may facilitate the management of cardiovascular risk factors and concomitant diseases advocated by current guidelines, 22 in addition to appropriately approach risk stratification for ischemic stroke 37 with institution of an adequate antithrombotic treatment. 38,39 Moreover, observational studies suggested that SA is associated with a reduced efficacy of catheter-and pharmacological-based rhythm control strategies, and that treatment with continuous positive airway pressure has a positive impact on AF recurrences after electrical cardioversion and improves catheter ablation outcomes.…”
Section: Follow-up and Af Occurrencementioning
confidence: 99%